Methodical experiments on the study of gas release from materials of thermonuclear reactor blankets - Zaurbekova, Zh.A.; Askerbekov, S.K.; Shaimerdenov, A.A.; Akhanov, A.M.; Chikhray, Y.V.; Kizane, G.; Tolenova, A.U. (Recent Contributions to Physics, 2021)
The work is devoted to the problem related to the development of methods for conducting irradiation experiments with tritium-generating materials of fusion reactor blanks. The experiments were carried out on a facility designed to study the release of tritium from lithium ceramics, which is located at the WWR-K reactor (Almaty, Kazakhstan). A special irradiation ampoule device was developed, in which samples of lithium ceramics are placed in reactor experiments. Due to the fact that the total length of the irradiation device is about 5 m and during irradiation, samples are installed in the lower part of the device, where pressure control is technically not possible, out-of-pile methodological experiments were conducted, during which calibration coefficients were determined that link gas flows from the area of investigated samples to the installation with partial pressures recorded in the mass spectrometer area. The results of neutron-physical, thermophysical and vacuum calculations showed that with the developed ampoule design, irradiation can be carried out at temperatures of 773-1473 K and that the developed installation can register the gas flow in the system at the operating level of tritium and helium in the studied samples above 10-11 mol/s. Key words: blanket, fusion reactor, lithium ceramics, tritium, helium.